2018
DOI: 10.1111/imb.12375
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA‐1 gene, tci‐miR‐1‐3p, is involved in cyflumetofen resistance by targeting a glutathione S‐transferase gene, TCGSTM4, in Tetranychus cinnabarinus

Abstract: microRNA-1 (miR-1) is a well-studied conservative microRNA (miRNA) involved in immune responses in mammals and insects. However, little is known about its role in pesticide resistance in arthropods. In this study, we found that a microRNA belong to miR-1 family (tci-miR-1-3p) was significantly down-regulated in a cyflumetofen-resistant strain (CYR) of Tetranychus cinnabarinus compared with its homologous susceptible strain (SS), indicating an involvement of miR-1 in cyflumetofen resistance in mites. One glutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 48 publications
(66 reference statements)
1
45
0
1
Order By: Relevance
“…All three genes showed the similar tendency for their expressions: increasing with the resistance development and decreasing with the resistance recession, in which the TcGSTm02 emerged the most sensitivity against the resistance change (its expression changed with significance from one resistant stage to the next) (Fig. ) and the part function of TcGSTm04 was investigated in the previous study of cyflumetofen‐resistant regulation by a miRNA . Therefore, TcGSTm02 was selected as the representative candidate to carry out the further functional study.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…All three genes showed the similar tendency for their expressions: increasing with the resistance development and decreasing with the resistance recession, in which the TcGSTm02 emerged the most sensitivity against the resistance change (its expression changed with significance from one resistant stage to the next) (Fig. ) and the part function of TcGSTm04 was investigated in the previous study of cyflumetofen‐resistant regulation by a miRNA . Therefore, TcGSTm02 was selected as the representative candidate to carry out the further functional study.…”
Section: Resultsmentioning
confidence: 68%
“…Together, these experiments strongly indicated that TcGSTm02 protein could catalyze GS − to bind with cyflumetofen. Another GST gene, TcGSTm04 (46.61% amino acid similarity with TcGSTm02 ), had been studied in T. cinnabarinus, of which the recombinant protein was shown to metabolize cyflumetofen. The decomposition rate against cyflumetofen was higher with TcGSTm02 compared to TcGSTm04, suggesting that TcGSTm02 has a higher relative contributiones to the observed cyflumetofen‐resistance levels in T. cinnabarinus .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations